2013
DOI: 10.1002/uog.12510
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome after fetoscopic release of amniotic bands: a single‐center experience and review of the literature

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 21 publications
3
49
0
2
Order By: Relevance
“…The hypothesis that pseudoamniotic bands after laser therapy for TTTS could be treated by fetoscopic amniotic band release is interesting, and it must be discussed to salvage the limb from definitive functionality loss or amputation. An experimental study on sheets in 1995 showed benefits for the intrauterine release of amniotic bands, 22 and to date, 19 cases in humans have been published, [23][24][25][26][27][28][29][30][31][32][33] with 58% having full functional recovery of the constricted limb after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that pseudoamniotic bands after laser therapy for TTTS could be treated by fetoscopic amniotic band release is interesting, and it must be discussed to salvage the limb from definitive functionality loss or amputation. An experimental study on sheets in 1995 showed benefits for the intrauterine release of amniotic bands, 22 and to date, 19 cases in humans have been published, [23][24][25][26][27][28][29][30][31][32][33] with 58% having full functional recovery of the constricted limb after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that it is not the band that changes, it is rather the child that grows and consequently the band appears to become tighter. One-staged radical excision of the constrictions, together with debulking, that is, the removal of the skin flap with overgrown pathologic tissue, restored normal blood supply, and stopped progression of the deformity [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic bands are now being successfully released fetoscopically through minimally invasive surgery [19]. The intrauterine procedure is delicate and the decision to perform this surgery must be carefully weighed against the potential risks to the mother and the fetus versus continuing or terminating pregnancy [2124]. …”
Section: Discussionmentioning
confidence: 99%